An ethical study of the impact hedonistic-utilitarianism exerts on the philosophy and practice of physician-assisted suicide - Ashlock, Larry Coleman (2005)
Terminal illness and the prospect of a painful and protracted dying process created new medical realities for Western culture in recent decades. Patients challenged traditional medical canons against medical killing by requesting changes in laws to allow physician assistance with suicide (PAS). This challenge occurred within a broader cultural context where core principles of medical common morality (beneficence, patient autonomy, and justice) were questioned. A new study of medical killing is warranted because ethical changes are occurring in current issues surrounding doctors and patients (for example, humanism and autonomy, rights, justice, and the morality of medical killing). Furthermore PAS proponents argue that sometimes there is a moral obligation for beneficent medicine to allay suffering; that is, a doctor must kill or assist his patient’s suicide. This thesis explores the possible influence that John Stuart Mill’s hedonistic-utilitarianism (HU) exerts on one aspect of medical killing, the philosophy and practice of PAS. This study clarifies certain features of the PAS debate and demonstrates weaknesses inherent in HU that impact adversely on medical canons and doctor-patient relationships (DPR). Six features within the PAS debate are examined for HU influence. Chapter 1 delineates how Mill’s key utilitarian pleasure-is-happiness (PH) theme interacts with the topic of PAS in contemporary medico-cultural discussions. Chapter 2 surveys some epochal events in the development of rights, justice, and medical killing, while chapter 3 surveys similarly autonomy, physician paternalism, and sanctity of life (SL)~all in relationship to PAS. The final chapter isolates key HU weaknesses found in PAS arguments and offers moral concerns regarding the utilisation of HU claims to justify changing traditional medical canons to endorse PAS. The thesis contributes to the ongoing medical-ethical dialogue about medical killing by exploring the historical and ethical points crucial to future discussions of medical killing